Plasmodium malariae and Plasmodium ovale infections and their association with common red blood cell polymorphisms in a highly endemic area of Uganda. (6th April 2019) - Subissi, Lorenzo; Kanoi, Bernard N; Balikagala, Betty; Egwang, Thomas G; Oguike, Mary; Verra, Federica; Proietti, Carla; Bousema, Teun; Drakeley, Chris J; Sepúlveda, Nuno
Abstract: Background: Plasmodium ovale and Plasmodium malariae infections are scarcely studied in sub-Saharan Africa, where the Plasmodium falciparum species predominates. The objective of this study is to investigate the prevalence of P. ovale and P. malariae infections and their relationship with common red blood cell polymorphisms in a cohort of 509 individuals from Uganda. Methods: Three cross-sectional surveys were conducted in individuals of 1–10 and >20 y of age from the Apac district at baseline and 6 and 16 weeks after drug treatment. Malaria infections were assessed by polymerase chain reaction and genotyping was performed for the sickle-cell allele, α-thalassaemia and glucose-6-phosphate dehydrogenase. Results: At baseline, the prevalence of infection was 7.5%, 12.6% and 57.4% for P. ovale, P. malariae and P. falciparum species, respectively. Co-infections were present in 14.1% of individuals, all including P. falciparum parasites. In children 1–5 y of age, the prevalence of P. ovale mono-infections increased significantly from 1.7% to 7.3% over time (p=0.004) while the prevalence of P. malariae and P. falciparum infections declined significantly during this study. After adjusting for confounding and multiple testing, only α-thalassaemia had a statistically significant increase in the odds of P. falciparum infections (odds ratio 1.93 [95% confidence interval 1.26 to 2.94]). Conclusions: Common red blood cell polymorphisms do not show strong effects on mild Plasmodium infections in this Ugandan population. To understand the extent of this result, similar studies should be carried out in other populations using larger cohorts.